EFFECTIVENESS OF THE REHABILITATION PROCESS IN THE FEMALE PRISON SYSTEM: THE IMPACTS ON SOCIAL REINTEGRATION BASED ON AN ANALYSIS OF THE DOCUMENTARY FLOWERS OF PRISON - Paulino , Fernanda Kelly Moreira; Brito, Maria Victoria Souza Gonçalves; de Souza Junior , Mario Cleone; Delfim, Priscila Martins (Seven Editora, 2025)
This paper aims to propose a reflection on how the resocialization process of women rendered invisible in the Brazilian prison system occurs. To this end, a case study of the film Flores do Cárcere (2019), directed by Paulo Caldas and Bárbara Cunha, which reflects the proposed theme, was carried out. For a better understanding of the elucidated theme, bibliographic research was used, based on knowledge already produced in the scientific community, from the analysis of doctrines, articles published on the subject, as well as the analysis of current legislation, allowing us to conclude that, like Xakila, Mel, Dani, Ana Pérola, Charlene - Chachá, and Rosa, protagonists of the documentary, countless other women lose their identity upon entering the prison system and, unfortunately, do not have access to public policies that allow for reintegration into society.DOI: https://doi.org/10.56238/sevened2025.040-004